Effect of heat treatment on the microstructures and mechanical properties of thixoformed graphene-reinforced aluminium alloy composite - Omar, Mohd Zaidi; Md Ali, Afifah; Salleh, Mohd Shukor; Hashim, Hanizam; Wakhi Anuar, Nur Farah Bazilah; Mohamed, Intan Fadhlina (Springer Nature, 2024)
The microstructure and the mechanical properties of heat-treated thixoformed graphene-reinforced aluminium alloy composite Al–7.0 wt% Si–0.3 wt% Mg reinforced with graphene nanoplatelets (GNP) produced by thixoforming has been investigated. The fabricated composite was further subjected to conventional T6 and short T6 (ST6) heat treatment. The thixo-ST6 condition involved 1 h of solution treatment at 540 C, followed by water quenching and 2 h of artificial ageing at 180 C. Microstructural revealed the formation of well refined and spherodisation of eutectic Si phase with an average size when subjected to thixo-ST6 heat treatment, along with the presence of uniformly dispersed GNP particles during thixoforming, effectively inhibits the grain growth and recrystallisation. The thixoST6 heat-treated sample exhibited improved strength, with a maximum yield strength of 281 MPa and an ultimate tensile strength of 326 MPa, compared to the thixo-T6 sample which achieved 219 MPa and 239 MPa, respectively. The results suggest potential benefits for the automotive industry, where lightweight materials with improved strength are highly desirable. The combination of thixoforming and ST6 heat treatment can be considered as a promising approach for the production of high-performance aluminium alloy composites, particularly for automotive applications.